'Uninformed and impractical'? The convict probation system and its impact upon the landscape of 1840s Van Diemen's Land. Issue 1 (2nd January 2020) - Tuffin, Richard; Gibbs, Martin
Abstract: The probation system was a form of convict management unique to the colony of Van Diemen's Land (Tasmania). In operation between 1839 and 1853, it has been derided by contemporary and modern opinion as an abject failure that nearly drove a colony bankrupt and hastened the end of Britain's great transportation project. Yet, probation has left an indelible mark upon the landscape of Tasmania. Through a massive expansion of the public works system, land was cleared and prepared for settlement, roads were built, and labour provided to free settlers. The colony that emerged from the 1840s formed a template upon which modern Tasmania was built. Using historical and archaeological methodologies, this paper creates a historical framework for engaging with the physicality of these probation places. In the process, it seeks to begin the recovery of a legacy that is today often ignored.